2017
DOI: 10.1371/journal.pone.0187447
|View full text |Cite|
|
Sign up to set email alerts
|

The treatment of femoral neck fracture using VEGF-loaded nanographene coated internal fixation screws

Abstract: PurposePrevious studies have proved that vascular endothelial growth factor (VEGF) has a dual role in the promotion of new bone formation and blood vessel repair during fracture healing. However, how to introduce VEGF to a fracture site safely and effectively is still a challenge. This study aimed to prepare a VEGF-loaded nanographene coated internal fixation screw and to evaluate its effects in the treatment of femoral neck fracture.MethodsNanographene coated screws were prepared by direct liquid-phase exfoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…[31] As material science advances, the composition of bone screws is undergoing continual evolution. Recent studies have demonstrated that the use of a new porous Ta-coated SiC (pTa-SiC) scaffold [32] and a vascular endothelial growth factor loaded nanographene-coated internal fixation screw [33] can enhance bone healing. Despite these promising results, questions remain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31] As material science advances, the composition of bone screws is undergoing continual evolution. Recent studies have demonstrated that the use of a new porous Ta-coated SiC (pTa-SiC) scaffold [32] and a vascular endothelial growth factor loaded nanographene-coated internal fixation screw [33] can enhance bone healing. Despite these promising results, questions remain.…”
Section: Discussionmentioning
confidence: 99%
“…[38] However, more recent studies have focused on the material and surgical approach of INFNF. For instance, the utilization of a new pTa-SiC scaffold [32] and a vascular endothelial growth factor loaded nanographene-coated internal fixation screw [33] has been demonstrated to enhance bone healing. While the availability of relevant clinical studies remains limited, the development of materials science is expected to lead to more studies in this area.…”
Section: Discussionmentioning
confidence: 99%
“…VEGF is relevant for bone formation, influencing vascularization and differentiation of bone and endothelial cells, and the absence of typically active forms of VEGF in bone formation may result in reduced initial calcification (39). In addition, VEGF increases bone fracture healing speed and bone neoformation area (40).…”
Section: Discussionmentioning
confidence: 99%
“…While conventional surgical interventions can realign the fracture fragments, they fall short in re-establishing the native vascular integrity. Techniques such as bone flap transplantation, bone marrow aspirations, and VEGF (Vascular Endothelial Growth Factor) implantation serve as indirect modalities to revascularize the femoral head, showing potential in attenuating the postoperative incidence of avascular necrosis [ [5] , [6] , [7] ]. Nonetheless, the prolonged treatment duration, substantial costs, and variable efficacy curtail their universal adoption.…”
Section: Introductionmentioning
confidence: 99%